THE GUIDELINES MANAGEMENT FOR DRIVING THE MARKETING STRATEGY TO THE SUCCESS OF THE CHICKEN FARMING EQUIPMENT BUSINESS IN A CLOSED SYSTEM FARM IN THAILAND - Pansumrit, Krit (Journal of Buddhist Anthropology, 2020)
The objective of this research is to study 1) Good Characteristics of Closed System Farm Chicken Equipment Operators 2) The Influence of Factors Affecting the Marketing Success of the Closed System Farm Chicken Equipment Business 3) Management guidelines for driving the marketing strategy to success. The population is business entrepreneurs. And those working in a chicken raising business In the upper central region such as Pathum Thani, Saraburi, Phra Nakhon Si Ayutthaya, Nonthaburi, Lop Buri, Chai Nat, Sing Buri and Ang Thong. The formula of Crazy and Morgan was used for 385 people using stratified sampling. By dividing the population into provinces and sampling from all provinces proportionally using simple random methods and interviewed 2 groups of key informants, 8 of which are 1) scholars and experts in closed-system farming animals 2) closed-loop farm equipment business operators. The tool is a questionnaire and interview form. The statistics used were mean and standard deviation. And inferential statistics Used to analyze data on the test of the influence of initial variables and dependent variables using multiple regression coefficients. The results of the research showed that 1) Good characteristics of business operators, including independence in management. Highest average 2) Influence of good characteristics of entrepreneurs Management of business and business marketing strategies Affects the marketing success of the chicken farm equipment business in a closed system. 3) Management guidelines for driving the marketing strategy for the success of the closed-system chicken farm equipment business Operators of the closed-system chicken farm equipment business must constantly change their work styles for the benefit of customers and businesses, using modern tools, machinery or technology to help produce products or services, produce Products are priced lower than other providers. And build good relationships with customers Raw material sellers and competitors.